Phenytoin induced Stevens Johnson syndrome: a case report - Pendurthi, Bharadwaja (International Journal of Basic & Clinical Pharmacology, 2018)
Stevens-Johnson syndrome (SJS) is a rare consequence of hypersensitivity reaction precipitated by certain drugs and viral infections. It is an idiosyncratic drug reaction usually associated with drugs like anti-epileptics, non-steroidal anti-inflammatory compounds and antibiotics. The overall incidence of this entity is very low and is life-threatening if undiagnosed and untreated. The syndrome is characterized by purpuric macules and bullous eruptions involving the mucous membrane which may be followed by systemic manifestations. The mechanism of SJS due to drugs is not fully defined. Delayed Hypersensitivity reaction mediated by T lymphocytes in response to a drug is thought to be responsible. Here authors present a case of SJS induced by phenytoin in an adult male. The case warrants the need of adopting a meticulous approach while prescribing phenytoin. The case is being reported to accentuate the importance of adverse drug reactions and to emphasize the importance of reporting such reactions ensuring efficient pharmacovigilance.